(untitled) (Journal Of Educational and Psychological Researches, 2023)
The aim of the research is to design educational software based on Web Quests and to measure its effectiveness in developing information search skills of students at the Department of Educational and Psychological Sciences. The research is experimental in nature using pre-post measurement. The research sample consisted of (91) male and female students from the second grade in the Department of Educational and Psychological Sciences, they were divided into two equal groups; the experimental group consisted of (47) students who adopted the educational software as a studying method, and the control group consisted of (44) students who follow the traditional method. The researchers prepared a list of skills for searching information and they designed an educational program based on Web Quests. The results of the research concluded that the students of the experimental group outperformed the students of the control group in both the cognitive and practical tests of skills for searching information. The results confirm the effectiveness of educational software based on Web Quests in developing information search skills.